The factors affecting mortality in intensive care unit of burn center - Osman Esen; Taner Turgut; Cagri Tiryaki; Mustafa Burc Yazicioglu; Ali Ciftci; Hayrunisa Kahraman Esen; Admin (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the characteristics of patients, mortality-affecting factors and mortality rate in follow-up burn-injured patients in an intensive care setting at a burns treatment centre. Method: The retrospective study was conducted between May and November 2014 at Kocaeli Derince Training and Research Hospital Burn Treatment Centre, Kocaeli, Turkey, and comprised data from January 2008 to January 2013 of in-patients who had been treated at the intensive care unit. The therapy outcomes and the follow-up processes were evaluated. Data was analysed using SPSS 17. Results: Of the 381 patients, 105(27.6%) were females and 276(72.4%) were males. The overall mean age was 28.4±21.1 years. There were 52(13.6%) mortalities, while 329(86.4%) survived. The mean total body surface area was 18.3±12.9% in those who survived compared to 52±24.3% in those who died (p<0.000). The highest rate of death was observed in those aged >66 years (p<0.000). The impact of flame burns on mortality was statistically significant (p<0.05). The impact of inhalation burns, suicide, abuse, operational requirements and systemic disease on mortality was statistically significant (p<0.05). Conclusions: Older age, higher total body surface area, flame burns, presence of inhalation burn, third degree burn, suicide attempt, presence of systemic disease, duration of prolonged mechanical ventilation and operation requirements were found to be poor prognostic factors for survival in burn patients. Key Words: Burn, Mortality, Risk factors, Intensive care, Burn centre.